Notes about Some General Principles of Law: A View of Some General Principles and Their Influence on The Law of Obligations in Colombian Legal Experience - Chamie, José Félix (2018)
This paper is intended to address in a synthetic way but with recent citations of the doctrine and jurisprudence some general principles of law, in order to contribute to the systematization, content, and affirmation of the general principles of law, and so, achieve the goal of a better law, the development of legal science and the progress of society. This paper makes particular emphasis on Colombian law, but it is projected as well inside the civil law tradition.